2013
DOI: 10.4300/jgme-d-12-00158.1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Specification of the Entrustment Process

Abstract: Never trust anything that can think for itself if you can't see where it keeps its brain. JK Rowling, Harry Potter and the Chamber of Secrets Funding: The authors report no external funding source for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…We propose department or specialty as a possible unit of analysis. This might be explored via ethnographic study followed by empirical studies that compare specialists’ entrustment decisions in response to different trust scenarios [38]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose department or specialty as a possible unit of analysis. This might be explored via ethnographic study followed by empirical studies that compare specialists’ entrustment decisions in response to different trust scenarios [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Cianciolo and Kegg [38] present a model of effective entrustment decision-making which focuses on understanding and improving supervisors’ risk-mitigation strategies. They propose that effective entrustment decisions could be reached by relying more on trainee observations and by accounting for subjective factors such as supervisors’ characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this editorial, they include a perspective on the entrustment process, 11 an exploration of the attributes of competence that enable entrustment decisions, 12 and a succinct description in one of this issue's Rip Outs. 13 Hauer et al 14 and Shaughnessy et al 15 applied the EPA concept to internal medicine and family medicine and identified 30 and 76 EPAs, respectively.…”
mentioning
confidence: 99%
“…These included experience, technical performance, presence of a generic competency, and training. 4,12,15,16 Experience relates to residents' experience in performing a specific task; technical performance refers to their skill in performing the activity; generic competency focuses on whether the justification for entrustment pays attention to 1 of the generic competency domains; and training relates to justifications based on skills training that a resident has had for the activity for which entrustment is requested. This initial list was adjusted during data sampling to develop the final template.…”
Section: Bottom Linementioning
confidence: 99%
“…4,12,15 In practice, entrustment decisions likely are influenced by informal assessments, supervisor characteristics, and the demands of the clinical situation. 16 Yet, little research has been done about how entrustment decisions are reached in daily practice 17 and whether generic competencies play a role. Consequently, there is a lack of evidence showing whether the introduction of EPAs has expanded the role of generic competencies in these decisions and in feedback provided to residents.…”
Section: Introductionmentioning
confidence: 99%